Doubling of farmers income through front line demonstrations of castor in Ananthapuramu district: Doubling of farmers income through front line demonstrations of castor in Ananthapuramu district - PAVAN KUMAR REDDY YERASI; AV S DURGA PRASAD; G D SATISH KUMAR; B SAHADEVA REDDY; G SURESH; J JAWAHAR LAL; C LAVANYA (Journal of Oilseeds Research, 2023)
The cluster frontline and frontline demonstrations were implemented in castor crop during kharif 2021-22 by AICRP on Castor, Agricultural Research Station, Ananthapuramu district of Andhra Pradesh to evaluate the performance of ICH-66 and package of practices on production and productivity of castor. Total of 100 demonstrations were executed during kharif, 2021 under rainfed conditions in Ananthapuramu district covering 26 villages and 14 mandals on Castor with different crop management modules of castor. In the Ananthapuramu district all most all mandals received the excess rainfall during the season. The results indicated that with improved practice there is a significant improvement in the seed yield, gross, net returns and B:C ratio compared with farmer’s practice.